Diversity of cephalopod from selected division of Sarawak, Malaysia. - Mohd Rubaie, Zulshafiq; Idris, Mohd Hanafi; Abu Hena, Mustafa Kamal; Wong, Sing King (2012)
The diversity of cephalopod from nine divisions at Sarawak, Malaysia was studied from August 2010 to February 2011. Cephalopod was collected from landing stations and local wet markets of Kuching, Sri Aman, Sibu, Sarikei, Mukah, Miri, Limbang, Lawas and Bintulu. Seven species of cephalopod belongings to three families were identified during the study period. The family Loliginidae was dominated group of cephalopod which consists of three species namely Uroteuthis (Photololigo) edulis, Uroteuthis (Photololigo) chinensis and Sepioteuthis lessoniana and recorded from five divisions. The species of cuttlefishes (Family Sepiidae) were Sepia recurvirostra, Sepia aculeate and Sepiella inermis and recorded from Sarikei, Kuching and Bintulu. Octopodidae was the only one species named Cistopus indicus and found in Bintulu. The diversity of cephalopod was found highest in Bintulu with seven species while surprisingly no species of cephalopod was recorded from Limbang, Lawas and Mukah. Study suggests that the findings of this study could be useful for future reference and detail study on cephalopod in the coastal water of Sarawak, Malaysia.